(untitled) (Bangladesh Journal of Nutrition, 2018)
A quasi experimental study was carried out among 80 unmarried adolescent girls living in a slum of Dhaka city to disseminate nutrition education messages for the improvement of nutritional knowledge and awareness. Base line information about socio-economic condition, food consumption pattern, sanitary and hygiene practices, nutritional knowledge of unmarried adolescent girls were collected by administering a pre tested questionnaire. One poster was formulated and practical food demonstration was also made for better understanding of the message. Effect of the nutrition education intervention was made in terms of pre test and post test knowledge. The monthly income of most of the respondent’s family (37.5%) falls into 6001-9000 taka while 25% of family expense less than 6000 per month. Only17.5% of the family spends more than Tk. 5000 per month on food consumption. The study shows that before intervention 88.8% respondents washed hands before eating, 73.8% respondents washed hands before cooking in food preparatory phase while after intervention both hand washing practice before eating and food preparatory phase were incremented to 100%. Respondent’s knowledge about feeding practice in pre and post test shows that only 1.2% of the respondent had proper knowledge and 31.2% had partial knowledge about exclusive breast feeding while after intervention 95% of the respondents had proper knowledge about exclusive breast feeding. Only 8.8% of the respondents thought that colostrum feeding are mandatory for child which was changed to 93.8% after intervention. Before intervention only 15%, 7.5% and 20% of the adolescent girls had correct knowledge about energy yielding, body building and body protecting food respectively. After intervention 93.8%, 90% and 96.2% of respondents had correct knowledge about these three food groups. The improvement of knowledge about feeding practices and functional food groups was found to be statistically significant (P <0.005). Bangladesh J. Nutr. Vol. 28-31, December 2018, P: 01-07